Simulations of the propagation of high-intensity laser pulses in discharge-ablated capillary waveguides - Spence, D; Hooker, S (Optical Society of American (OSA), 2000)
We present the results of simulations of the propagation of high-intensity laser pulses in discharge-ablated capillary waveguides. The limitations of this type of waveguide for pulse intensities of the order of 1016 W cm-2 are discussed. However, for higher intensities we describe a new regime of quasi-matched guiding, that results in significant improvements in guiding performance. The effect on quasi-matched guiding of changing the atomic numbers of the atoms that compose the plasma waveguide is discussed. Calculations are presented for boron capillaries that show quasi-matched guiding over lengths of 32 mm for an input intensity of 5 × 10 17 Wcm-2. © 2000 Optical Society of America.